2006
DOI: 10.1590/s0073-47212006000400009
|View full text |Cite
|
Sign up to set email alerts
|

Rotifera das zonas limnética e litorânea do reservatório de Tapacurá, Pernambuco, Brasil

Abstract: Rotifera from littoral and pelagic zones of Tapacurá reservoir, Pernambuco, Brazil. The rotifers of Tapacurá reservoir, State of Pernambuco, Brazil, were studied concerning the horizontal distribution in pelagic and littoral zones, in the rainy (August/2003) and dry seasons (January/2004). Qualitative and quantitative samples were carried out in nictimeral samplings in the different zones of the reservoir, with an interval of six hours in the two depths. Biotic parameters as richness, density, diversity and eq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
1
12

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 2 publications
(1 reference statement)
2
11
1
12
Order By: Relevance
“…Neste trabalho, foram estudados quatro ecossistemas, incluindo dois ambientes lóticos (rio Brígida e uma parte do rio São Francisco). Em seguida, uma série de trabalhos foi desenvolvida nas quatro regiões do estado de Pernambuco (Bouvy et al 2001, Almeida 2002, Melo Júnior 2002, Moura 2004, Almeida et al 2006, Melo Júnior, dados não publicados), todos em reservatórios.…”
Section: Resultsunclassified
See 3 more Smart Citations
“…Neste trabalho, foram estudados quatro ecossistemas, incluindo dois ambientes lóticos (rio Brígida e uma parte do rio São Francisco). Em seguida, uma série de trabalhos foi desenvolvida nas quatro regiões do estado de Pernambuco (Bouvy et al 2001, Almeida 2002, Melo Júnior 2002, Moura 2004, Almeida et al 2006, Melo Júnior, dados não publicados), todos em reservatórios.…”
Section: Resultsunclassified
“…Espera-se, entretanto, que o número de espécies dessas e de outras famílias possa aumentar bastante, quando forem realizados inventários mais completos com maior cobertura geográfica das regiões Amazônica, Nordeste e Centro-oeste (Rocha, dados não publicados). A maioria dos trabalhos utilizou rede com 65 micrômetros de abertura de malha (Tabela 1), entretanto, estudos realizados no Brasil têm demonstrado que um maior número de espécies de rotíferos planctônicos límnicos é registrado quando redes com abertura de malha menor que esta são utilizadas (Lucinda et al 2004, Almeida et al 2006, Rocha, dados não publicados). A riqueza de rotíferos de Pernambuco é aparentemente bastante inferior à encontrada em outros Estados brasileiros, tais como Mato Grosso (Neves et al 2003 (Aoyagui & Bonecker 2004).…”
Section: Resultsunclassified
See 2 more Smart Citations
“…However, the maximum diversity was observed at the sampling point without vegetation in early December 2011, with the caveat that most species recorded that day were not typical of the plankton. Almeida et al (2006), studying rotifers in Tapacurá reservoir (Pernambuco), also found significant participation of nonplanktonic taxa in the vegetation-free zone, and the authors related this fact to wind action (which brings up individuals from the bottom), precipitation (which carries various organisms from the margin) and floating macrophytes (moved by wind action and may influence biological communities across the surface of the water column, being an efficient mean of transportation for organisms related to them).…”
Section: Discussionmentioning
confidence: 96%